Higher Frequency of Undetected Acute Coronary Syndrome in Elderly Patients with Chest Pain Who Visited the Emergency Department: A Large-Cohort Retrospective Study. (10th April 2021) - Hong, Ki Hun; Bae, Sung Jin; Lee, Dong Hoon; Lee, Choung Ah.; Park, Sang Hyun; Kim, Duk Ho; Kim, Eui Chung; Lim, Jee Yong; Han, Sangsoo; Choi, Yoon Hee
Abstract : Background . Acute coronary syndrome (ACS) is a critical disease encountered in the emergency department (ED). Despite the development of diagnostic tools, it may be difficult to diagnose ACS because of atypical symptoms and equivocal test results. We investigated the difference in the rates of revisit and undetected ACS between adult and elderly patients who visited the ED with chest pain. Method . Data from 11, 323 patients who visited the ED with chest pain at university hospitals in Korea were retrospectively analyzed. The cohort was categorized into two age groups: the adult (30–64 years) and elderly (>65 years). Baseline characteristic data (age, sex, vital signs, triage category, etc.) were obtained. We selected patients who revisited the ED within 30 d and investigated whether ACS was diagnosed. Result . The revisit rate was higher in the elderly (12%) than in the adult group (8.3%). The rate of undetected ACS among the revisited patients was 2.91% (18/7, 186) in adults and 6.08% (16/1, 998) in elderly patients. Conclusion . Elderly patients with chest pain had an increased rate of ED revisits and undetected ACS than adult patients. We recommend that old patients should be hospitalized to observe the progression of cardiac complaints or receive short-term follow-up.